40 years of immunization in Mozambique - Cassocera, Marta (2021)
Funding Information: We would like to thank the Calouste Gulbenkian Foundation and the Flandres Government (Building Institutional Capacity at the Mozambique INS – BICMINS) from where M. Cassocera has a PhD scholarship; Fundo Nacional de Investigação-Moçambique and German Research Foundation (DFG) from where A. Chissaque has scholarship. Sousa Ribe and Orvalho Augusto for the inputs and clarifications regarding the Expanded Program on Immunization. Publisher Copyright: © 2020 Fundacao Oswaldo Cruz. All rights reserved.